On BCL-Algebra - Al-Kadi, Deena Sobhi; Hosny, Rodyna Ahmed (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
It has been found that the BCL-algebra is more extensive class than BCK/BCI/BCH algebra. In this paper we study some properties of BCL-algebra of type (2,0) We also find deformation of such algebra and illustrate the connection between divisible algebra and deformation function.